Marketing Communications of the Yogyakarta City Tourism Office in Introducing Kotabaru as a Cultural Heritage Area and Green City - Mulawarman Krisna; Rosilawati Yeni; Rafique Zain; Iqbal Khatami Muhammad (E3S Web of Conferences)
The city of Yogyakarta, one of the famous tourism destinations in Indonesia, has recorded significant growth in tourist visits. One of the main attractions of Yogyakarta City Tourism is the Kotabaru Yogyakarta Residential Area. Branding strategy efforts have been carried out by the Yogyakarta City Tourism Office introducing the Kotabaru Residential Area as a cultural heritage area and Garden City. The research method used is a qualitative method with data collection through desk reviews and interviews with related parties. The government has taken concrete steps to increase tourist attraction through various events and festivals, as well as infrastructure development and promotion plans. The government were carried out Kotabaru’s potential with various initiatives, ranging from the evening event “Good Night Kotabaru” to cultural festivals such as the “Kotabaru Heritage Festival”. These events aim to introduce the rich culture and history of Kotabaru to the local community Kotabaru has the potential to become an attractive and sustainable tourist destination if its historical and cultural potential is maximized properly. The steps taken by the government are positive steps in raising this potential. Thus, cross-sector collaboration and local community involvement need to be increased to achieve this goal.